1981
DOI: 10.1152/ajpregu.1981.241.5.r370
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride-sensitive ammonium and sodium ion transport in the blue crab

Abstract: In the estuarine crab, Callinectes sapidus, net NH4+ efflux was twice as high in animals acclimated to 17% salinity seawater (SW) (0.495 +/- 0.084 mumol . h-1 . g wet wt-1, n = 7) than in animals acclimated to full-strength 35% SW (0.212 +/- 0.028 mumol . h-1 . g-1, n = 7). Amiloride (3 X 10(-4) M) in the external SW reversibly inhibited these effluxes by 63 +/- 6% (n = 6) and 67 +/- 6% (n = 5), respectively. Unidirectional Na+ influx was reversibly inhibited 42 +/- 6% (n = 7) by amiloride in 17% SW-acclimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 0 publications
1
28
1
3
Order By: Relevance
“…Since then, our understanding of how ammonia actually permeates the gills has become less and less clear, as various studies have led to conflicting conclusions. Evidence has been presented to reinforce the predominance of Na + /NH 4 + exchange (Maetz, 1973;Kerstetter and Keeler, 1976;Payan and Girard, 1978;Pressley et al, 1981;McDonald and Prior, 1988;McDonald and Milligan, 1988), whereas others have argued for the dominance of simple NH 3 diffusion down the partial pressure NH 3 gradient maintained by the CO 2 hydration reaction in the gill boundary layer (Cameron and Heisler, 1983;Wilson et al, 1994;Wilkie and Wood, 1994 (Avella and Bornancin, 1989;Heisler, 1990), or mixed mechanisms whereby ammonia moves partly by diffusion and partly by electroneutral exchange (Wright and Wood, 1985;Salama et al, 1999). The overall problem is that ammonia excretion has often been experimentally correlated with Na + uptake and/or with acid excretion, but both the stoichiometry and stability of the couplings have been variable and inconsistent among and within studies.…”
Section: Retrospection On Past Controversiesmentioning
confidence: 97%
“…Since then, our understanding of how ammonia actually permeates the gills has become less and less clear, as various studies have led to conflicting conclusions. Evidence has been presented to reinforce the predominance of Na + /NH 4 + exchange (Maetz, 1973;Kerstetter and Keeler, 1976;Payan and Girard, 1978;Pressley et al, 1981;McDonald and Prior, 1988;McDonald and Milligan, 1988), whereas others have argued for the dominance of simple NH 3 diffusion down the partial pressure NH 3 gradient maintained by the CO 2 hydration reaction in the gill boundary layer (Cameron and Heisler, 1983;Wilson et al, 1994;Wilkie and Wood, 1994 (Avella and Bornancin, 1989;Heisler, 1990), or mixed mechanisms whereby ammonia moves partly by diffusion and partly by electroneutral exchange (Wright and Wood, 1985;Salama et al, 1999). The overall problem is that ammonia excretion has often been experimentally correlated with Na + uptake and/or with acid excretion, but both the stoichiometry and stability of the couplings have been variable and inconsistent among and within studies.…”
Section: Retrospection On Past Controversiesmentioning
confidence: 97%
“…The process that these crustaceans uses to eliminate ammonia is active excretion. Ammonia excretion rates are correlated with Na + absorption (Pressley et al, 1981, Harris et al, 2001). NH 4 + substitutes for K+ in the activation of the ouabain-sensitive Na + / K + -ATPase, which is located in the basolateral membranes of the gill epithelium cells (Towle et al, 1981;Towle & Kays, 1986).…”
Section: Histological Effectsmentioning
confidence: 99%
“…Since then many studies have been carried out attempting to delineate the mechanisms involved in ammonia excretion and Na + uptake. However, these studies often led to conflicting conclusions: some supported the presence of a Na + /NH 4 + exchange system (Maetz and GarciaRomeu, 1964;Maetz, 1973;Kerstetter and Keeler, 1976;Payan, 1978;Pressley et al, 1981;McDonald and Prior, 1988;McDonald and Milligan, 1988), others suggested that diffusive mechanisms predominated (Avella and Bornancin, 1989;Wilson et al, 1994;Wilkie and Wood, 1994;Wilkie et al, 1996), while still others argued that both mechanisms were likely to be present (Wright and Wood, 1985;Heisler, 1990;Salama et al, 1999).…”
Section: Introductionmentioning
confidence: 99%